Empowerment-based intervention and immigrant awareness of biomedical HIV prevention tools in France - (:unkn) unknown (My University, 2023)
Abstract Background Sub-Saharan African immigrants are particularly affected by HIV in France and social hardship is an indirect factor of HIV acquisition. While biomedical HIV prevention tools are available for HIV prevention, evidence suggests a lack of knowledge of these tools among immigrants from Sub-Saharan Africa. We analysed the impact of an empowerment-based intervention on the knowledge of treatment as prevention (TasP), Pre Exposure Prophylaxis (PrEP) and Post Exposure Prophylaxis (PEP) among a population of precarious sub-Saharan African immigrants. Methods Data were collected in the Makasi research project. Participants were recruited in public places based on their precarious situations, they were randomised into two groups (intervention and control) followed during six months between 2018 and 2021. We described the knowledge of biomedical HIV prevention tools at each follow-up time (0, 3, 6 months) and used random-effects logistic regression models to analyse the intervention effect on the level of knowledge of these tools. Results The majority of the participants were men (77.5%) and almost half of them arrived in France within 2 years prior to inclusion (49.3%). At the time of inclusion, 56% of participants knew about TasP, 6% knew about PEP and 4% knew about PrEP. Receiving the intervention increased the odds of knowing PEP (aOR=2.02 [1.09-3.75]; p < 0.026). Intervention effect were observed for TasP and PrEP only after 6 six months. We observed significant time effect for PEP (at 3 months aOR=4.26 [2.33-7.80]; p < 0.001; at 6 months aOR=18.28 [7.39-45.24]; p < 0.001) and PrEP (at 3 months aOR=4.02 [2.10-7.72]; p < 0.001; at 6 months aOR=28.33 [11.16-71.91]; p < 0.001). This time effect is linked to the associations outreach activities. Conclusions Our results suggest that exposure to the Makasi intervention combined with associations activities contributed to
Keywords: African Research